Bronchioloalveolar carcinoma with metastasis to the pituitary gland: a case report. - Lau, G (1998)
An unusual case of metastatic bronchioloalveolar carcinoma of the lung presented as a pituitary tumour in a young adult Chinese female, who subsequently died after having undergone trans-sphenoidal resection. Metastatic cancers of the pituitary are uncommon even in necropsy series and rarely give rise to clinical symptoms. This case draws attention to the fact that, although uncommon, pituitary metastases have been noted with increasing frequency and their distinction from primary pituitary tumours is often difficult. A metastatic pituitary tumour may be the initial presentation of an unknown primary malignancy, wherein the metastatic deposits may also be limited to the pituitary gland. Clinicians and pathologists alike should consider a metastatic lesion in the differential diagnosis of a non-functioning pituitary tumour.